2011
DOI: 10.5483/bmbrep.2011.44.8.529
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein S3 is phosphorylated by Cdk1/cdc2 during G2/M phase

Abstract: Ribosomal protein S3 (rpS3) is a multifunctional protein in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…For instance, RPs are phosphorylated throughout the mammalian cell cycle and contain the consensus kinase recognition site for CDK1 [19,42], a kinase that orchestrates essential steps of mitosis [42,43]. Additional evidence lies in work exploring CDK1 activity, which was found to phosphorylate Rps3/uS3 in vitro [44]. Interestingly, ribosome profiling across cell cycle stages revealed that specific transcripts are preferentially translated during different stages of the cell cycle, even though translation is globally repressed [45,46].…”
Section: Phosphorylated Ribosomes In Sickness and In Healthmentioning
confidence: 99%
“…For instance, RPs are phosphorylated throughout the mammalian cell cycle and contain the consensus kinase recognition site for CDK1 [19,42], a kinase that orchestrates essential steps of mitosis [42,43]. Additional evidence lies in work exploring CDK1 activity, which was found to phosphorylate Rps3/uS3 in vitro [44]. Interestingly, ribosome profiling across cell cycle stages revealed that specific transcripts are preferentially translated during different stages of the cell cycle, even though translation is globally repressed [45,46].…”
Section: Phosphorylated Ribosomes In Sickness and In Healthmentioning
confidence: 99%
“…We believe that this huge increase in protein phosphorylation at the start of mitosis is responsible for causing all of the structural changes associated with mitosis. Many other studies have identified hundreds of mitotic phosphoproteins, and most of them are likely phosphorylated by CDKs (10-12). However, much is still unclear about how these phosphorylation events are regulated and coordinated to ensure an ordered cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%
“…This phosphorylation occurs at T221 and is important for the nuclear translocation of hRpS3 (21). Here, we studied the interaction between hRpS3 and Cdk2 (Fig.…”
Section: Discussionmentioning
confidence: 99%